Lilies not for me [videorecording (DVD)] - O'Shea, Fionn; Aramayo, Robert, 1992-; Kellyman, Erin (Gravitas Ventures, 2025)
A gay novelist tells his psychiatric nurse the story of a relationship with an old friend which spiraled out of control when they turned to a risky procedure to 'cure' their forbidden feelings for one another.